Contaminated interaction: another barrier to circular material flows - Baxter,W; Aurisicchio,M; Childs,PRN (Journal of Industrial Ecology, 2017)
Contamination poses a significant problem to the circular economy (CE), which derives much of its value from maintaining pure material flows. The aim of this article is to frame contaminated interaction among other forms of contamination and investigate its effects on the CE. The research is based on a review of the contamination literature and case studies. We differentiate between three types of contamination influencing circular material flows: technical, which deals with fitness for use; systemic, which deals with efficiency in processing; and interaction, which deals with user-object interaction and decision making. Our focus is on developing a foundational understanding of contaminated interaction and how it influences circular processes. Through multiple examples, contaminated interaction is shown to create three barriers to the CE: downcycling, disposal, and hindered circulation. Among other proposals to address contaminated interaction, the research calls for the development of experientially transferrable design—products that can move between users and uses without negative consequences.